One hundred new species of lichenized fungi: A signature of undiscovered global diversity - Lumbsch, H. Thorsten; Ahti, Teuvo; Altermann, Susanne; de Paz, Guillermo Amo; Aptroot, André; Arup, Ulf; Peña, Alejandrina Bárcenas; Bawingan, Paulina A.; Benatti, Michel N.; Betancourt, Luisa; Björk, Curtis R.; Boonpragob, Kansri; et al. (My University, 2011)
The number of undescribed species of lichenized fungi has been estimated at roughly 10,000. Describing and cataloging these would take the existing number of taxonomists several decades; however, the support for taxonomy is in decline worldwide. In this paper we emphasize the dire need for taxonomic expertise in lichenology. We bring together 103 colleagues from institutions worldwide to describe a total of 100 new species of lichenized fungi, representing a wide taxonomic and geographic range. The newly described species are: Acarospora flavisparsa, A. janae, Aderkomyces thailandicus, Amandinea maritima, Ampliotrema cocosense, Anomomorpha lecanorina, A. tuberculata, Aspicilia mansourii, Bacidina sorediata, Badimia multiseptata, B. vezdana, Biatora epirotica, Buellia sulphurica, Bunodophoron pinnatum, Byssoloma spinulosum, Calopadia cinereopruinosa, C. editae, Caloplaca brownlieae, C. decipioides, C. digitaurea, C. magnussoniana, C. mereschkowskiana, C. yorkensis, Calvitimela uniseptata, Chapsa microspora, C. psoromica, C. rubropulveracea, C. thallotrema, Chiodecton pustuliferum, Cladonia mongkolsukii, Clypeopyrenis porinoides, Coccocarpia delicatula, Coenogonium flammeum, Cresponea ancistrosporelloides, Crocynia microphyllina, Dictyonema hernandezii, D. hirsutum, Diorygma microsporum, D. sticticum, Echinoplaca pernambucensis, E. schizidiifera, Eremithallus marusae, Everniastrum constictovexans, Fellhanera borbonica, Fibrillithecis sprucei, Fissurina astroisidiata, F. nigrolabiata, F. subcomparimuralis, Graphis caribica, G. cerradensis, G. itatiaiensis, G. marusa, Gyalideopsis chicaque, Gyrotrema papillatum, Harpidium gavilaniae, Hypogymnia amplexa, Hypotrachyna guatemalensis, H. indica, H. lueckingii, H. paracitrella, H. paraphyscioides, H. parasinuosa, Icmadophila eucalypti, Krogia microphylla, Lecanora mugambii, L. printzenii, L. xanthoplumosella, Lecidea lygommella, Lecidella greenii, Lempholemma corticola, Lepraria sekikaica, Lobariella sipmanii, Megalospora austropacifica, M. galapagoensis, Menegazzia endocrocea, Myriotrema endoflavescens, Ocellularia albobullata, O. vizcayensis, Ochrolechia insularis, Opegrapha viridipruinosa, Pannaria phyllidiata, Parmelia asiatica, Pertusaria conspersa, Phlyctis psoromica, Placopsis imshaugii, Platismatia wheeleri, Porina huainamdungensis, Ramalina hyrcana, R. stoffersii, Relicina colombiana, Rhizocarpon diploschistidina, Sticta venosa, Sagenidiopsis isidiata, Tapellaria albomarginata, Thelotrema fijiense, Tricharia nigriuncinata, Usnea galapagona, U. pallidocarpa, Verrucaria rhizicola, and Xanthomendoza rosmarieae. In addition, three new combinations are proposed: Fibrillithecis dehiscens, Lobariella botryoides, and Lobariella pallida.
Keywords: Darwin declaration; Encyclopedia of life; Global taxonomy initiative; Lichens; Taxonomic impediment; Taxonomy